Polycomb and polyhomeotic are constituents of a multimeric protein complex in chromatin of Drosophila melanogaster. - Franke, A (1992)
The polycomb group (Pc-G) genes are responsible for maintaining the repressed state of homeotic genes during development. It has been suggested that the Pc-G exerts its transcriptional control by regulating higher order chromatin structure. In particular, the finding of genetic and molecular similarities to components involved in heterochromatin formation, led to the proposal that homeotic genes are permanently repressed by mechanisms similar to those responsible for heterochromatin compaction. Because of synergistic effects, Pc-G gene products are thought to act in a multimeric complex. Using immunoprecipitation we show that two members of the Pc-G, Polycomb and polyhomeotic, are constituents of a soluble multimeric protein complex. Size fractionation indicates that a large portion of the two proteins are found in a distinct complex of molecular weight 2-5 x 10(6) Da. During embryogenesis the two proteins show the same spatial distribution. In addition, by double-immunofluorescence labelling we can demonstrate that Polycomb and polyhomeotic have exactly the same binding patterns on polytene chromosomes of larval salivary glands. We propose that some Pc-G proteins act in multimeric complexes to compact the chromatin of stably repressed genes like the homeotic regulators.